Role of hysterosalpingography and diagnostic laparoscopy in infertility - Sachdeva, Parminder Kaur; Kaur, Navdeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Infertility is one of the commonest problems encountered in gynecology. Improved familiarity with and access to infertility services among the affluent and better educated patients probably accounts for their greater use of the medical resources. The two most important diagnostic procedures which are used for evaluation of infertility are hysterosalpingography (HSG) and laparoscopy. Methods: The present study was conducted on 50 patients with infertility after meeting inclusion criteria in the Department of Obstetrics and Gynaecology and Department of Radio-diagnosis, in Maharishi Markandeshwar Institute of Medical Sciences and Research, Mullana, Ambala over a period of 18 months. All the patients were examined by HSG as part of their routine infertility evaluation, three months after HSG, status were assessed by laparoscopy. All the data collected were presented in terms of frequencies and percentage. Chi-square and p value were calculated in excel. P <0.05 was considered statistically significant. Results: The study included 50 female patients with infertility. Among them 34 (68%) patients belonged to primary infertility and 16 (32%) belongs to secondary infertility. 58% of patients were in the age group between 20-25 years, 28% in between 26-30 and 14% with age above 30 years. Maximum number of cases 29 (58%) had duration of infertility between 1-5 years. Of the 50 patients, 31 cases had normal HSG findings and 19 cases had abnormal findings. 15 patients were dropped from the study during the period of laparoscopy. On laparoscopy 7 (20%) patients were observed with uterine abnormalities, 15 (43%) with tubal factors, 10 (29%) with ovarian defects, 7 (20%) with peritoneal factors and 4 (11%) with unknown etiology. On HSG and laparoscopy 7 patients had shown some complications. Conclusions: Although laparoscopy is a superior method of detection of tubal and pelvic pathologies in the evaluation of infertility, HSG is more economical, highly sensitive and elementary method, suitable for evaluation of endometrial and tubal pathologies. These two methods are not alternative but are complimentary techniques.